Characterization and manipulation of the bacterial community in the midgut of Ixodes ricinus - Guizzo, Melina Garcia; Dolezelikova, Kristyna; Neupane, Saraswoti; Frantova, Helena; Hrbatova, Alena; Pafco, Barbora; Fiorotti, Jessica; Kopacek, Petr; Zurek, Ludek (Parasites & vectors, 2022)
BACKGROUND: Ticks are obligate hematophagous arthropods transmitting a wide range of pathogens to humans and animals. They also harbor a non-pathogenic microbiota, primarily in the ovaries and the midgut. In the previous study on Ixodes ricinus, we used a culture-independent approach and showed a diverse but quantitatively poor midgut bacterial microbiome. Our analysis also revealed the absence of a core microbiome, suggesting an environmental origin of the tick midgut microbiota. METHODS: A bacterial analysis of the midgut of adult females collected by flagging from two localities in the Czech Republic was performed. Using the culture-independent approach, we tested the hypothesis that the midgut microbiome is of the environmental origin. We also cultured indigenous bacteria from the tick midgut and used these to feed ticks artificially in an attempt to manipulate the midgut microbiome. RESULTS: The midgut showed a very low prevalence and abundance of culturable bacteria, with only 37% of ticks positive for bacteria. The culture-independent approach revealed the presence of Borrelia sp., Spiroplasma sp., Rickettsia sp., Midichloria sp. and various mainly environmental Gram-positive bacterial taxa. The comparison of ticks from two regions revealed that the habitat influenced the midgut bacterial diversity. In addition, the midgut of ticks capillary fed with the indigenous Micrococcus luteus (Gram-positive) and Pantoea sp. (Gram-negative) could not be colonized due to rapid and effective clearance of both bacterial taxa. CONCLUSIONS: The midgut microbiome of I. ricinus is diverse but low in abundance, with the exception of tick-borne pathogens and symbionts. The environment impacts the diversity of the tick midgut microbiome. Ingested extracellular environmental bacteria are rapidly eliminated and are not able to colonize the gut. We hypothesize that bacterial elimination triggered in the midgut of unfed adult females is critical to maintain low microbial levels during blood-feeding.
Keywords: Ixodes ricinus; Capillary feeding; klíště; mikrobiota; Česká republika; Microbiome manipulation; Microbiota; Rickettsia; Czech Republic; Animals; ženské pohlaví; Culturing; zvířata; High-throughput sequencing; Ixodes; Borrelia; Midgut; Female; Microbiome